Phenotypic changes of γδ T cells in Plasmodium falciparum placental malaria and pregnancy outcomes in women at delivery in Cameroon - Nana, Chris Marco Mbianda; Tchakounté, Bodin Darcisse Kwanou; Bitye, Bernard Marie Zambo; Fogang, Balotin; Zangue, Berenice Kenfack Tekougang; Seumko’o, Reine Medouen Ndeumou; Nana, Benderli Christine; Leke, Rose Gana Fomban; Djontu, Jean Claude; Argüello, Rafael José; Ayong, Lawrence; Megnekou, Rosette (Frontiers in Immunology, 2024)
.Introduction: Depending on the microenvironment, γδ T cells may assume characteristics similar to those of Th1, Th2, Th17, regulatory T cells or antigen presenting cells. Despite the wide documentation of the effect of Th1/Th2 balance on pregnancy associated malaria and outcomes, there are no reports on the relationship between γδ T cell phenotype change and Placental Malaria (PM) with pregnancy outcomes. This study sought to investigate the involvement of γδ T cells and its subsets in placental Plasmodium falciparum malaria. Methods: In a case-control study conducted in Yaoundé, Cameroon from March 2022 to May 2023, peripheral, placental and cord blood samples were collected from 50 women at delivery (29 PM negative: PM- and 21 PM positive: PM+; as diagnosed by light microscopy). Hemoglobin levels were measured using hemoglobinometer. PBMCs, IVBMCs and CBMCs were isolated using histopaque-1077 and used to characterize total γδ T cell populations and subsets (Vδ1+, Vδ2+, Vδ1-Vδ2- ) by flow cytometry. Results: Placental Plasmodium falciparum infection was associated with significant increase in the frequency of total γδ T cells in IVBMC and of the Vδ1+ subset in PBMC and IVBMC, but decreased frequency of the Vδ2+ subset in PBMC and IVBMC. The expression of the activation marker: HLA-DR, and the exhaustion markers (PD1 and TIM3) within total γδ T cells and subsets were significantly up-regulated in PM+ compared to PM- group. The frequency of total γδ T cells in IVBMC, TIM-3 expression within total γδ T cells and subsets in IVBMC, as well as HLA-DR expression within total γδ T cells and Vδ2+ subset in IVBMC were negatively associated with maternal hemoglobin levels. Furthermore, the frequency of total γδ T cells in PBMC and PD1 expression within the Vδ2+ subset in CBMC were negatively associated with birth weight contrary to the frequency of Vδ1-Vδ2- subset in PBMC and HLA-DR expression within the Vδ2+ subset in IVBMC which positively associated with maternal hemoglobin level and birth weight, respectively. Conclusion: The data indicate up-regulation of activated and exhausted γδ T cells in Plasmodium falciparum placental malaria, with effects on pregnancy outcomes including maternal hemoglobin level and birth weight.